A ballistic composite armor and method of making the same. - Wong, Shaw Voon (2007)

(untitled)
The present invention provides a ballistic armor (1) which includes a composite inner layer (3) and outer layers (2, 4) that surround the composite inner layer (3) on its front and/ or back portion. The outer layers (2, 4) are secured to the front and/ or back portion of the composite inner layer (3) with an adhesive. The outer layers (2, 4) include a suitable projectile-fragmenting material that will cause a projectile impacting the outer layer (2, 4) to blunt and dissipate the load over a wide area. The composite inner layer (3) includes a suitable material that provides high impact energy dissipation due to a fracture and damage. Accordingly,the composite inner (3) layer will fracture during impact and the extent of the fracture or rubblization is maximized but contained by the surrounding outer layers.